Treating alcohol use disorder in the absence of specialized services – evaluation of the moving inpatient Treatment Camp approach in Uganda - Verena Ertl (BMC, 2021)
Abstract Background The gap between service need and service provision for alcohol-related disorders is highest in resource-poor countries. However, in some of these contexts, local initiatives have developed pragmatic interventions that can be carried out with limited specialized personnel. In an uncontrolled treatment study, we aimed to evaluate the feasibility, acceptability, safety, costs and potential effects of an innovative locally developed community-based program (the Treatment Camp) that is based on an inpatient clinic that moves from community to community. Methods Out of 32 treatment-seeking individuals 25 took part in the one-week Treatment Camp that included detoxification and counseling components. Re-assessments took place 5 and 12 months after their participation. We explored the course of a wide range of alcohol-related indicators, using the Alcohol Use Disorders Identification Test (AUDIT) as primary outcome complemented by a timeline follow-back approach and the Obsessive Compulsive Drinking Scale. Additionally, we assessed impaired functioning, alcohol-related stigmatization, symptoms of common mental health disorders and indicators of family functioning as reported by participants’ wives and children. Results All alcohol-related measures decreased significantly after the Treatment Camp and remained stable up to the 12-month-assessment with high effect sizes ranging from 0.89 to 3.49 (Hedges’s g). Although 92% of the participants had lapsed at least once during the follow-up period, 67% classified below the usually applied AUDIT cutoff for hazardous drinking (≥ 8) and no one qualified for the dependent range (≥ 20) one year after treatment. Most secondary outcomes including impaired functioning, alcohol-related stigmatization, symptoms of depression and indicators of family functioning followed the same trajectory. Conclusions We found the Treatment Camp approach to be acceptable, feasible, safe and affordable (approx. 111 USD/patient) and we could obtain preliminary evidence of its efficacy. Due to its creative combination of inpatient treatment and monitoring by medical personnel with local mobility, the Treatment Camp appears to be more accessible and inclusive than other promising interventions for alcohol dependent individuals in resource-poor contexts. Effects of the approach seem to extend to interactions within families, including a reduction of dysfunctional and violent interactions.